Sustainability Signals in Emerging Markets: The Effect of ESG Disclosure and Profitability on Stock Returns with Firm Size as a Moderator (Evidence from LQ45 Index, 2020–2024) - Shita Debby Fardeliah; Jeni Susyanti; Mohamad Bastomi (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure and Return on Assets (ROA) on stock returns, with firm size as a moderating variable, in companies listed in the LQ45 index during the 2020–2024 period. The research adopts a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample consists of 24 firms selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that ESG disclosure and ROA have a positive and significant effect on stock returns. ROA emerges as the most dominant factor, highlighting that profitability remains a primary signal for investors in the Indonesian capital market. Firm size also has a positive effect on stock returns. In terms of moderation, firm size does not moderate the relationship between ESG disclosure and stock returns, but it strengthens the effect of ROA on stock returns. These findings suggest that profitability signals from larger firms are perceived as more credible by investors, while the impact of ESG disclosure is consistent regardless of firm size. This study contributes to the sustainable finance literature and provides practical implications for investors, corporate management, and capital market regulators.